2015
DOI: 10.1080/15226514.2015.1045133
|View full text |Cite
|
Sign up to set email alerts
|

High Accumulation and Subcellular Distribution of Thallium in Green Cabbage (Brassica OleraceaL.Var. CapitataL.)

Abstract: The accumulation of thallium (Tl) in brassicaceous crops is widely known, but both the uptake extents of Tl by the individual cultivars of green cabbage and the distribution of Tl in the tissues of green cabbage are not well understood. Five commonly available cultivars of green cabbage grown in the Tl-spiked pot-culture trials were studied for the uptake extent and subcellular distribution of Tl. The results showed that all the trial cultivars mainly concentrated Tl in the leaves (101∼192 mg/kg, DW) rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In case of exposure to air-borne contamination (fly ash), thallium may also enter the human body via lungs. Recent reports indicate that high thallium concentrations may be found in green vegetables, such as cabbage (Ning et al 2015) or kale (Wallace 2015). A significant increase in thallium content was also observed in case of opioid abusers with mean level of 21 μg L −1 , compared to 1 μg L −1 in the control group (Ghaderi et al 2015).…”
Section: Distribution Of Thallium In the Environmentmentioning
confidence: 99%
“…In case of exposure to air-borne contamination (fly ash), thallium may also enter the human body via lungs. Recent reports indicate that high thallium concentrations may be found in green vegetables, such as cabbage (Ning et al 2015) or kale (Wallace 2015). A significant increase in thallium content was also observed in case of opioid abusers with mean level of 21 μg L −1 , compared to 1 μg L −1 in the control group (Ghaderi et al 2015).…”
Section: Distribution Of Thallium In the Environmentmentioning
confidence: 99%
“…Contamination with thallium is effected on the environmental and human health. Thallium has toxic effect even at sub ppb concentration and accumulate in plant, vegetables, fruit, microorganisms, animals and human tissues due to water soluble [4,5]. The occupational exposure of thallium is 0.1 mg m -2 for skin and more than 15 mg m -2 is dangerous for human.…”
Section: Introductionmentioning
confidence: 99%
“…Studies only focused on theoretical inference, leaching experimental research under non-planting conditions and non-acid rain conditions [30,31,32,33]. For example, Ning et al [34] suggested that all the heavy metals in the soil were activated by chelating agents, but only some of them were absorbed by plants. So, it is theoretically inferred that there is a risk of multiple HMs leaching.…”
Section: Introductionmentioning
confidence: 99%